Training leaders in the United States Army - Johnson, Haskell Lee 1920- (1954)
The military education process for United States Army leaders was presented in this study.
Mimeographed.
Vita.
Thesis (M.A.)--University of the Philippines, Diliman.
Keywords: United States. -- Army; Leadership